Observation of the Emperor penguins Aptenodytes forsteri in the Prince Gustav Channel related with unusual sea-ice decline in north-western Weddell Sea - Hrbáček, Filip Hrbáček; Smolíková, Jana; Nývlt, Daniel; Kavan, Jan; Engel, Zbyněk (Revista de Biología Marina y Oceanografía, 2019)
A pair of juvenile emperor penguins (Aptenodytes forsteri) was observed in the northern coast of James Ross Island, the north-western sector of the Weddell Sea, Antarctica, in January 2017. The penguins originated from the colony located on Snow Hill Island, 120-130 km far from the observation area. Despite the emperor penguin´s ability to migrate over long distances, when they are well-known from different areas in Antarctica, this was the first observation of this species in the north of James Ross Island. In this short paper we discuss the environmental factors which allowed the penguins to reach James Ross Island northern coast, especially significant sea ice variability in this area during last decade.